Computational fluid dynamics of patient-specific coronary artery during stent treatment - Nur Syuhada, Che Amdilah; Lau, Yu Shi; Liew, Yih Miin; Wan Naimah, Wan Ab Naim; Mohd Jamil, Mohamed Mokhtarudin (IET, 2022)
Coronary artery disease is usually treated using stent treatment. However, restenosis is one of the major limitations of using stent. Local hemodynamics can be the main indicator of the occurrence of restenosis. In this project, a computational fluid dynamics (CFD) analysis is performed on a stented coronary artery patient with a 12-month follow-up post stent in order to determine the potential occurrence of restenosis in the patient. An OCT image of the coronary artery is taken and ethically approved from Universiti Malaya Medical Centre (UMMC). Firstly, a 3D geometry of the coronary artery will be developed using image segmentation procedure. The stent structure is smoothened within the coronary artery. Then, the geometry is meshed and CFD analysis is applied. The blood is assumed as a non-Newtonian fluid following a Carreau model of fluid viscosity. The inlet is applied with a velocity waveform, while the outlet is set as zero pressure. Lastly, the time averaged wall shear stress (TAWSS) is calculated. The region with TAWSS < 0.4 Pa is identified as a potential location for restenosis. From our simulations, the location in the middle of the stent shows TAWSS < 0.4 Pa, showing the potential of restenosis in the patient.